FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PERTOLONGAN PERSALINAN OLEH TENAGA KESEHATAN DI WILAYAH KERJA PUSKESMAS KUTA BULUH TAHUN 2016 - Elsarika Damanik; Masriati Panjaitan; Imelda Sinaga (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Deliveries by health personnel is an important factor in efforts to reduce maternal mortality. Deliveries by health personnel in the work area by 76.8% Kuta buluh health centers are still below the target of 87.5% Labuhanbatu Selatan regency. The purpose of this study was to determine the factors associated with the selection of delivery helper in the work area Kuta buluh Health Center South Labuhanbatu in 2015. The study was a descriptive study with a design study is a cross sectional. Variables examined as the dependent variable is the labor helpers while independent variables are age, maternal education, parit, prenatal care, maternal-class participation, cost, distance/access to health care facilities and husband support. The data in this study using primary data and secondary data. Sampling by simple total sampling is based on a list of names from register cohort maternal mother. Data collection by using a questionnaire given to mothers who birth in January to December 2015 was selected as the sample. Analysis of data using univariate and bivariate test with chi square test. The results showed that 71% of births attended by skilled health and 29% are not helped by medical personnel. The results of the bivariate data analysis showed a statistically significant variables associated with the selection of auxiliary labor is knowledge, mother's attitude, maternal-class participation and husband support